Composite lithium battery diaphragm and preparation method thereof
By designing an annular high-strength frame structure on the lithium-ion battery separator and using inorganic ceramic particle coatings of different particle sizes, the problem of thermal shrinkage of the separator under high temperature conditions is solved, the mechanical strength and filtration efficiency are improved, and the safety and performance of the battery are enhanced.
Patent Information
- Application Number
- CN202411984027.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-01
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing lithium-ion battery separators are prone to heat shrinkage under high temperature conditions, which affects the safety and performance of the battery, and it is difficult for traditional methods to improve mechanical strength and filtration efficiency at the same time.
A composite lithium battery separator is designed, wherein one side of the base film is provided with a first region and an annular second region, the first region is coated with a first coating, the second region is coated with a second coating, and the particle size of the second inorganic particles is smaller than the first inorganic particles, forming an annular high-strength frame structure.
It improves the mechanical strength and coating strength of the diaphragm, reduces the heat shrinkage rate, takes into account mechanical strength, coating strength, thermal conductivity and filtration efficiency, and enhances the safety and performance of the battery.
Smart Images

Figure CN119742535A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of battery manufacturing, and in particular relates to a composite lithium battery diaphragm and a preparation method thereof. Background Art
[0002] As one of the core components of modern portable electronic devices and electric vehicles, the performance and safety of lithium-ion batteries are of vital importance. The main components of batteries include positive electrodes, negative electrodes, separators and electrolytes, among which the role of separators is particularly critical. It not only needs to ensure the effective transmission of lithium ions, but also should have good mechanical strength, thermal stability and chemical stability to ensure the safe operation of the battery. In recent years, the research direction of improving the performance of separators has focused on enhancing their ion conductivity, mechanical strength, heat resistance and chemical stability.
[0003] Lithium-ion battery testing usually includes electrical performance testing, safety performance testing, environmental adaptability testing, physical performance testing, self-discharge testing, cycle life testing and thermal abuse testing.
[0004] Thermal abuse testing of batteries, also known as thermal shock testing, is an important method for evaluating the safety of batteries under extreme conditions such as high temperature or short circuit by simulating extreme conditions such as high temperature or short circuit to strictly test the battery's tolerance under abnormal conditions. This test is mainly used in the battery industry, especially lithium-ion batteries, to detect their performance and safety under abnormal conditions. Studies have found that in thermal abuse testing of batteries, when the battery is in a temperature range above 100°C, the diaphragm inside the battery will shrink due to continuous heating.
[0005] In order to improve the thermal stability and safety of the diaphragm and increase the passing rate of the thermal abuse test, people have adopted a variety of methods, among which coating a layer of inorganic ceramic particles on the PP (polypropylene) or PE (polyethylene) diaphragm is considered to be the most effective and economical method. This ceramic diaphragm is based on PP, PE or a multi-layer composite diaphragm, and a layer of Al is coated on the surface. 2 O 3 (aluminum oxide), SiO 2 (Silicon dioxide), Mg(OH) 2 Or other inorganic ceramic particles with excellent heat resistance, after special process treatment, they are tightly bonded to the matrix, stably combining the flexibility of organic matter and the thermal stability of inorganic matter. The ceramic material is distributed in the three-dimensional structure of the diaphragm to form a specific rigid skeleton. With its extremely high thermal stability, it can effectively prevent the diaphragm from shrinking and melting under thermal runaway conditions, allowing the battery to withstand thermal abuse at 130°C or higher.
[0006] The influence of ceramic particle size on the diaphragm is mainly reflected in the following aspects:
[0007] ① Bonding degree: Ceramic particles with small particle size are more likely to adhere to the surrounding raw materials during the firing process to form a tight neck connection, thereby improving the density and mechanical strength of the ceramic film.
[0008] ②Filtration pressure drop: In ceramic particle filtration membranes, the reduction in the particle size of silicon carbide particles will greatly increase the filtration pressure drop. This is because the membrane made of small-size particles has smaller pores and a tighter structure, which causes the fluid to overcome greater resistance when passing through, resulting in a decrease in filtration efficiency. Too low filtration efficiency will accelerate the wear and aging process of the diaphragm and increase energy consumption.
[0009] ③ Thermal shrinkage: Ceramic particles with smaller particle sizes can reduce the thermal shrinkage of the diaphragm to a certain extent due to their higher specific surface area and better packing density. Compactly stacked nanoparticles can achieve better thermal shrinkage performance, i.e., small thermal shrinkage. As the thickness of the ceramic coating increases, the temperature at which thermal shrinkage starts will increase.
[0010] ④Coating strength: The coating support strength has an important influence on the thermal shrinkage performance of the base film. When the coating support strength is less than the thermal shrinkage stress of the base film, the thermal shrinkage performance of the lithium-ion battery ceramic coating film is poor; when the coating support strength is equal to or higher than the thermal shrinkage stress of the base film, the thermal shrinkage performance of the lithium-ion battery ceramic coating film will become better. The coating formed by ceramic particles with smaller particle size usually has higher strength and better support, which helps to improve the thermal shrinkage performance of the diaphragm.
[0011] ⑤ Thermal conductivity: Ceramic particles with smaller particle size have higher thermal conductivity, which is conducive to the conduction and distribution of heat, thereby improving the thermal stability of ceramic materials.
[0012] In short, although reducing the particle size of ceramic particles can improve mechanical strength, coating strength and thermal conductivity, it may also sacrifice filtration efficiency. Therefore, in the process of membrane preparation, the particle size of ceramic particles needs to be finely controlled to achieve the optimal balance of performance.
[0013] In actual production, in order to maintain the filtration efficiency of the diaphragm, the industry tends to use ceramic particles with larger particle sizes and increase the mechanical strength and support strength of the ceramic layer by increasing the thickness of the ceramic coating. However, with the development trend of lightweight and high-performance batteries, the traditional approach of increasing the thickness of the ceramic coating to improve mechanical strength has been difficult to meet demand. Although reducing the thickness of the diaphragm is conducive to lightweight batteries, it will weaken the mechanical strength and support strength of the ceramic layer, becoming a bottleneck restricting the improvement of battery performance.
[0014] Therefore, it is necessary to develop a composite lithium battery separator and a preparation method thereof to improve the above-mentioned shortcomings. Summary of the invention
[0015] In view of the deficiencies in the prior art, an object of the present invention is to provide a composite lithium battery separator and a preparation method thereof.
[0016] In order to achieve the above-mentioned invention object, the technical solution adopted by the present invention includes:
[0017] In one aspect, a composite lithium battery separator comprises: a base film, wherein at least one side of the base film is provided with a first region and an annular second region, wherein the first region is circular and the second region surrounds the first region; the first region is coated with a first coating and the second region is coated with a second coating;
[0018] The first coating layer includes first inorganic particles, the second coating layer includes second inorganic particles, the first inorganic particles and the second inorganic particles are both inorganic ceramic particles, and the particle size of the second inorganic particles is smaller than that of the first inorganic particles.
[0019] In the present invention, the annular second region surrounds the first region, so that the second coating layer can form an annular shape and surround the first coating layer.
[0020] In the present invention, the first region is circular, so that the first coating is circular, which is beneficial for uniform force on the first coating, thereby facilitating improvement of the mechanical strength of the composite lithium battery separator.
[0021] In the present invention, the base film is selected from one of polyethylene film, polypropylene film, polyethylene-polypropylene-polyethylene multilayer film, polypropylene-polyethylene-polypropylene multilayer film, cellulose film, polyethylene terephthalate non-woven film, polybutylene terephthalate non-woven film, polyimide non-woven film, polyamide non-woven film, polyvinyl chloride non-woven film, polytetrafluoroethylene non-woven film, and aromatic polyamide membrane.
[0022] In the present invention, the base film is specifically selected from a polyethylene film with a thickness of 9 μm and an air permeability of 50 to 300 s / 100 mL.
[0023] In the present invention, the particle size of the second inorganic particles is smaller than that of the first inorganic particles. When the first inorganic particles and the second inorganic particles are made of the same material, the thermal conductivity of the second coating layer is greater than that of the first coating layer.
[0024] Preferably, the first inorganic particle is selected from SrTiO 3 SnO 2 、CeO 2 , MgO, NiO, CaO, ZnO, ZrO 2 , Y 2 O 3 、Al 2 O 3 、TiO 2 、SiC、AlOOH、SiO 2One or more of .
[0025] In the present invention, the first inorganic particle is specifically selected from TiO 2 .
[0026] Preferably, the particle size of the first inorganic particles is 0.2 μm to 0.5 μm.
[0027] Preferably, the thickness of the first coating is 1 μm to 3 μm.
[0028] Preferably, the second inorganic particle is selected from SrTiO 3 SnO 2 、CeO 2 , MgO, NiO, CaO, ZnO, ZrO 2 , Y 2 O 3 、Al 2 O 3 、TiO 2 、SiC、AlOOH、SiO 2 One or more of .
[0029] In the present invention, the second inorganic particles are specifically selected from MgO, Al 2 O 3 One of them.
[0030] And / or, the particle size of the second inorganic particles is 0.05 μm to 0.3 μm.
[0031] And / or, the thickness of the second coating layer is 1 μm to 3 μm.
[0032] Preferably, the surface of the second coating is coated with the first coating.
[0033] Preferably, the thickness of the first coating in the first region is greater than the thickness of the first coating on the surface of the second coating, and the first coating on the surface of the second coating and the first coating in the first region together form a convex surface.
[0034] In the present invention, the first coating layer forms a convex surface, which is beneficial to improving the mechanical strength of the first coating layer.
[0035] Preferably, the thermal conductivity of the second coating is greater than that of the first coating.
[0036] Preferably, the second inorganic particles have various particle sizes.
[0037] On the other hand, a method for preparing a composite lithium battery separator comprises the following steps:
[0038] Preparing slurry: Preparing the first inorganic particles into a first slurry, and preparing the second inorganic particles into a second slurry;
[0039] Coating the first area: after covering the second area of the base film, coating the first slurry on the first area, then removing the cover and drying the base film to obtain an intermediate film;
[0040] Coating the second area: After covering the upper surface of the first coating layer of the intermediate film, coating the second slurry on the second area, then removing the covering and drying the base film to obtain a composite lithium battery separator.
[0041] In the present invention, the second slurry is applied after covering the upper surface of the first coating layer of the intermediate film. The second slurry can well cover the side of the first coating layer, so that after the second slurry solidifies to form the second coating layer, there will be no water-permeable gap between the second coating layer and the first coating layer. At the same time, the first coating layer and the second coating layer form a whole, which is beneficial to improving the strength of the coating layer on the surface of the base film.
[0042] Preferably, the drying temperature is 60°C to 90°C.
[0043] In the present invention, the drying temperature is specifically 75°C.
[0044] The main raw materials of the present invention are introduced as follows:
[0045] SrTiO 3 (Strontium titanate): It has good dielectric properties and can improve the insulation performance of the diaphragm; at the same time, it has high thermal stability and chemical stability.
[0046] SnO 2 (Tin dioxide): It has a high theoretical capacity and can be used as a negative electrode material in lithium-ion batteries. It can also be used as a separator coating to enhance its mechanical properties.
[0047] CeO 2 (Cerium dioxide): It has excellent redox stability, can prevent internal short circuits in the battery, and helps improve the safety performance of the battery.
[0048] MgO (magnesium oxide): has a high melting point and good chemical stability, which can effectively prevent internal short circuit of the battery and improve the safety of the battery.
[0049] NiO (nickel oxide): Although not usually the material of choice for separators, it can be used to improve the electronic insulation properties of the separator in some cases.
[0050] CaO (calcium oxide): Theoretically, it can improve the heat resistance of the separator, but in practice, due to its strong hygroscopicity, it is rarely used directly in lithium battery separators.
[0051] ZnO (zinc oxide): has good thermal stability and chemical stability, and can improve the mechanical strength of the diaphragm.
[0052] ZrO 2 (Zirconium dioxide): It has excellent thermal and chemical stability, and can significantly improve the heat resistance and mechanical strength of the diaphragm.
[0053] Y 2 O 3 (Yttrium oxide): can increase the high temperature resistance of the diaphragm and improve the safety and stability of the battery.
[0054] Al 2 O 3 (Alumina): is one of the most commonly used ceramic coating materials because it has excellent chemical stability and mechanical strength, can effectively prevent short circuits and improve the heat resistance of the diaphragm.
[0055] TiO 2 (Titanium dioxide): It has good chemical and thermal stability and can also be used as the negative electrode material of lithium-ion batteries. When used as a separator coating, it can improve the mechanical properties of the separator.
[0056] SiC (Silicon Carbide): Although mainly used in the semiconductor field, it is also sometimes considered for use in battery separators to improve its thermal conductivity and mechanical strength due to its high thermal conductivity and mechanical strength.
[0057] AlOOH (aluminum oxide): This material has good flame retardant properties and can be used to improve battery safety.
[0058] SiO 2 (Silicon dioxide): It has good insulation properties and chemical stability, and can improve the heat resistance and mechanical strength of the diaphragm.
[0059] Compared with the prior art, the advantages of the present invention include:
[0060] (1) In a composite lithium battery separator provided by the present invention, the particle size of the second inorganic particles is smaller than that of the first inorganic particles, so that the mechanical strength of the second coating is improved, and the annular second coating surrounds the first coating, and the second coating can form a high-strength frame structure, which is beneficial to improving the mechanical strength of the composite lithium battery separator, thereby facilitating reducing the thickness of the composite lithium battery separator;
[0061] (2) In the composite lithium battery separator provided by the present invention, the deformation of the edge of the base film is relatively large during the shrinkage process of the base film, and the annular second coating surrounds the first coating. Since the particle size of the second inorganic particles is smaller than that of the first inorganic particles, the bonding ability between the second coating and the base film is improved, so that the second coating can support the second region of the base film, which is beneficial to improving the coating strength;
[0062] (3) The composite lithium battery separator provided by the present invention has a first coating with a large particle size, which is beneficial to improving the filtration efficiency of the composite lithium battery separator; the first coating is surrounded by a ring-shaped second coating, which is beneficial to the high composite lithium battery separator taking into account mechanical strength, coating strength, thermal conductivity and filtration efficiency;
[0063] (4) In the composite lithium battery separator provided by the present invention, the particle size of the second inorganic particles is smaller than that of the first inorganic particles, which is beneficial to improving the thermal conductivity of the second coating layer, thereby reducing the accumulation of heat on the high-composite lithium battery separator, thereby reducing the temperature of the high-composite lithium battery separator during operation, and reducing the deformation of the base film due to shrinkage due to heat. BRIEF DESCRIPTION OF THE DRAWINGS
[0064] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0065] Figure 1 This is an overall schematic diagram of a composite lithium battery separator in Example 1 of the present invention;
[0066] Figure 2 This is a cross-sectional schematic diagram of a composite lithium battery separator in Example 1 of the present invention;
[0067] Figure 3 This is a cross-sectional schematic diagram of a composite lithium battery separator in Example 7 of the present invention.
[0068] Reference numerals:
[0069] 1. Base film; 2. First coating; 3. Second coating. DETAILED DESCRIPTION
[0070] In order to enable those skilled in the art to understand the characteristics and effects of the present application, the following is a general description and definition of the terms and expressions mentioned in the specification and claims. Unless otherwise specified, all technical and scientific terms used herein have the common meanings understood by those skilled in the art for the present application. In case of conflict, the definitions in this specification shall prevail.
[0071] The theories or mechanisms described and disclosed herein, whether correct or incorrect, should not limit the scope of the present application in any way, that is, the content of the present application can be implemented without being limited by any specific theory or mechanism.
[0072] As used herein, "this application" means "the present invention" or "the present disclosure".
[0073] The use of "one", "an", "a kind" or similar expressions to describe the components and technical features described in this application is merely for the convenience of expression and to provide a general meaning to the scope of this application. Therefore, such description should be understood to include one or at least one, and the singular also includes the plural, unless it is obvious that it refers to another meaning.
[0074] In this document, "or its combination" means "or any combination thereof", and "any one", "any one" means "any one", "any one" or "any one".
[0075] As used herein, the terms "comprises," "including," "having," "containing," or any other similar terms are open-ended transitional phrases that are intended to cover non-exclusive inclusions. For example, a composition or article containing multiple elements is not limited to the elements listed herein, but may also include other elements that are not explicitly listed but are generally inherent to the composition or article. In addition, unless otherwise expressly stated, the term "or" refers to an inclusive "or" rather than an exclusive "or." For example, any of the following situations satisfies the condition "A or B": A is true (or exists) and B is false (or does not exist), A is false (or does not exist) and B is true (or exists), and both A and B are true (or exist). In addition, in this article, the terms "comprising", "including", "having", and "containing" should be interpreted as being specifically disclosed and simultaneously covering closed conjunctions such as "consisting of", "consisting of", and "the remainder is", as well as conjunctions such as "consisting essentially of", "mainly consisting of", "mainly consisting of", "basically containing", "essentially consisting of", "essentially consisting of", and "essentially containing".
[0076] In this article, all features or conditions such as numerical values, quantities, contents and concentrations defined in the form of numerical ranges or percentage ranges are only for simplicity and convenience. Accordingly, the description of numerical ranges or percentage ranges should be deemed to have covered and specifically disclosed all possible sub-ranges and individual values within the range (including integers and fractions), especially integer values. For example, the range description of "1.0 to 8.0" or "between 1.0 and 8.0" or "between 1.0 and 8.0" should be deemed to have specifically disclosed all sub-ranges such as 1.0 to 8.0, 1.0 to 7.0, 2.0 to 8.0, 2.0 to 6.0, 3.0 to 6.0, 4.0 to 8.0, 3.0 to 8.0, etc., and should be deemed to cover endpoint values, especially sub-ranges defined by integer values, and should be deemed to have specifically disclosed individual values such as 1.0, 2.0, 3.0, 4.0, 5.0, 6.0, 7.0, 8.0, etc. Unless otherwise indicated, the foregoing method of interpretation applies to all contents of the entire application, regardless of whether the scope is broad or not.
[0077] If the quantity, concentration or other numerical value or parameter is expressed as a range, a preferred range (or a better range) or a series of upper and lower limits, it should be understood that all ranges consisting of any pair of the upper limit or preferred value (or a better value) of the range and the lower limit or preferred value (or a better value) of the range have been specifically disclosed herein, regardless of whether these ranges are disclosed separately. In addition, if a numerical range is mentioned herein, unless otherwise specified, the range should include its endpoints and all integers and fractions within the range.
[0078] In this document, numerical values should be understood to have the accuracy of the number of significant digits of the numerical value, provided that the purpose of the invention can be achieved. For example, the number 40.0 should be understood to cover the range of 39.50 to 40.49.
[0079] In this document, when Markush groups or optional terms are used to describe features or examples of the present application, those skilled in the art should understand that all subgroups or any individual elements in the Markush group or optional list can also be used to describe the present application. For example, if X is described as "selected from X 1 , X 2 and X 3 ", which also means that X is fully described as X 1 The claim that X is X 1 and / or X 2 and / or X 3Furthermore, in the case of using Markush groups or optional terms to describe features or examples of the present application, those skilled in the art should understand that any combination of subgroups or individual members of all elements in the Markush group or optional list can also be used to describe the present application. Accordingly, for example, if X is described as "selected from X 1 , X 2 and X 3 If Y is described as "selected from the group consisting of Y1, Y2 and Y3", it means that X is fully described as X. 1 and / or X 2 and / or X 3 And Y is Y 1 and / or Y 2 and / or Y 3 's claim.
[0080] Unless otherwise specified, in this application, a compound refers to a chemical substance formed by two or more elements connected by chemical bonds, including small molecule compounds and polymer compounds, but not limited thereto. The interpretation of a compound in this article is not limited to a single chemical substance, but can also be interpreted as the same type of chemical substances with the same composition or the same properties.
[0081] If not otherwise specified, in this application, polymer refers to the product formed by monomer through polymerization reaction, often including many polymer aggregates, each polymer is formed by many simple structural units repeatedly connected by covalent bonds, and monomer is a compound of synthetic polymer. Polymer can include homopolymer, copolymer, prepolymer, etc., and is not limited to this. Homopolymer refers to a polymer polymerized by a monomer. Copolymer includes random copolymer (structure is such as -AABABBBAAABBA-), alternating copolymer (structure is such as -ABABABAB-), graft copolymer (structure is such as -AA(A-BBBB)AA(A-BBBB)AAA-) and block copolymer (structure is such as -AAA AA-BBBBBB-AAAAA-) etc. Prepolymer refers to a polymer with a molecular weight between a monomer and a final polymer with a lower molecular weight, and the prepolymer contains reactive functional groups that can further undergo polymerization reaction to obtain a product with a higher molecular weight that is fully cross-linked or hardened. Polymer certainly includes oligomers, and is not limited to this. Oligomers, also known as low polymers, are polymers composed of 2 to 20 repeating units, usually 2 to 5 repeating units.
[0082] Unless otherwise specified, the "resin" in this application is a customary name for a synthetic polymer, which may include monomers, polymers thereof, combinations of monomers, combinations of polymers thereof, or combinations of monomers and polymers thereof, etc., and is not limited thereto.
[0083] If not otherwise specified, in the present application, modified products include products after modification of reactive functional groups of each resin, products after prepolymerization of each resin with other resins, products after crosslinking of each resin with other resins, products after copolymerization of each resin with other resins, and the like.
[0084] If not otherwise specified, the unsaturated bonds described in the present application refer to reactive unsaturated bonds, such as but not limited to unsaturated double bonds that can undergo cross-linking reactions with other functional groups, such as but not limited to unsaturated carbon-carbon double bonds that can undergo cross-linking reactions with other functional groups.
[0085] The unsaturated carbon-carbon double bonds described in the present application preferably include, but are not limited to, vinyl, vinylbenzyl, (meth)acryloyl, allyl or a combination thereof. Vinyl should be interpreted to include vinyl and vinylidene. (Meth)acryloyl should be interpreted to include acryloyl and methacryloyl.
[0086] Unless otherwise specified, the hydrocarbon groups described in this application include, but are not limited to, alkyl, alkenyl or alkynyl, and include their various isomers when interpreted. For example, a C1-C6 divalent hydrocarbon group is interpreted to include a C1-C6 divalent straight-chain hydrocarbon group, a C2-C6 divalent branched hydrocarbon group or a C3-C6 divalent cyclic hydrocarbon group. For another example, a propyl group should be interpreted to include n-propyl and isopropyl.
[0087] Unless otherwise specified, in this application, parts by weight represent relative parts by weight in a composition, which may be any weight unit, such as but not limited to kilograms, kilograms, grams, pounds, etc. For example, 100 parts by weight of polyphenylene ether resin may represent 100 kilograms of polyphenylene ether resin or 100 pounds of polyphenylene ether resin.
[0088] It should be understood that the features disclosed in the various embodiments herein may be arbitrarily combined to form the technical solution of the present application, as long as there is no contradiction in the combination of these features.
[0089] The present application will be described below with specific implementations and examples. It should be understood that these specific implementations and examples are merely illustrative and are not intended to limit the scope of the present application and its use.
[0090] Unless otherwise stated, the methods, reagents and conditions used in the following preparation examples, comparative examples and examples are conventional methods, reagents and conditions in the art.
[0091] In the following descriptions:
[0092] TiO 2 : Rutile type, active ingredient content ≥ 99.5%, including three particle sizes of 0.2μm, 0.3μm, and 0.5μm;
[0093] MgO: Active ingredient content ≥ 99.99%, including three particle sizes of 0.05μm, 0.15μm, and 0.3μm;
[0094] Sodium carboxymethyl cellulose: active ingredient content ≥ 99.99%;
[0095] Methyl acrylate: active ingredient content ≥99%;
[0096] Sodium polyacrylate: active ingredient content ≥99%.
[0097] Prepare the first cover sheet, the second cover sheet, the third cover sheet and the fourth cover sheet:
[0098] The first cover sheet is a plastic disc with a radius of 20 mm;
[0099] The second cover sheet is a rectangular frame with an outer side length of 50 mm and a through hole with a radius of 20 mm in the center.
[0100] The third covering sheet is a 40mm×40mm plastic sheet;
[0101] The fourth cover sheet is a square frame formed by four plastic strips connected in sequence, the width of the plastic strip is 5 mm, and the outer side length of the rectangular frame is 50 mm.
[0102] Preparation Example
[0103] Preparation Example 1
[0104] The raw materials used in this preparation example include: 40 parts of 0.2 μm TiO 2 , 8 parts of sodium carboxymethyl cellulose, 2 parts of methyl acrylate, 5 parts of sodium polyacrylate, and 45 parts of deionized water.
[0105] The preparation method of this preparation example includes:
[0106] Z1. Add deionized water, sodium carboxymethyl cellulose, sodium polyacrylate and methyl acrylate into the mixing cylinder of the mixing machine, and then stir at a speed of 1200 RPM until they are completely dissolved;
[0107] Z2. Add TiO to the mixing cylinder 2 , stir at a low speed of 500 RPM for 45 minutes, let it stand for degassing for 5 minutes, and sieve the material to obtain the first slurry.
[0108] Preparation Example 2
[0109] The difference between this preparation example and preparation example 1 is that: TiO 2 The particle size is 0.3 μm.
[0110] Preparation Example 3
[0111] The difference between this preparation example and preparation example 1 is that: TiO 2 The particle size is 0.5 μm.
[0112] Preparation Example 4
[0113] The raw materials used in this preparation example include: 40 parts of 0.05 μm MgO, 8 parts of sodium carboxymethyl cellulose, 2 parts of methyl acrylate, 5 parts of sodium polyacrylate, and 45 parts of deionized water.
[0114] The preparation method of this preparation example includes:
[0115] Z1. Add deionized water, sodium carboxymethyl cellulose, sodium polyacrylate and methyl acrylate into the mixing cylinder of the mixing machine, and then stir at a speed of 1200 RPM until they are completely dissolved;
[0116] Z2. Add MgO to the mixing cylinder, stir at a low speed of 500 RPM for 45 minutes, let it stand for degassing for 5 minutes, sieve the material to obtain the second slurry.
[0117] Preparation Example 5
[0118] The difference between this preparation example and preparation example 4 is that the particle size of MgO is 0.15 μm.
[0119] Preparation Example 6
[0120] The difference between this preparation example and preparation example 4 is that the particle size of MgO is 0.3 μm.
[0121] Preparation Example 7
[0122] The raw materials used in this preparation example include: 30 parts of 0.05 μm MgO, 10 parts of 0.15 μm MgO, 8 parts of sodium carboxymethyl cellulose, 2 parts of methyl acrylate, 5 parts of sodium polyacrylate, and 45 parts of deionized water.
[0123] The preparation method of this preparation example includes:
[0124] Z1. Add deionized water, sodium carboxymethyl cellulose, sodium polyacrylate and methyl acrylate into the mixing cylinder of the mixing machine, and then stir at a speed of 1200 RPM until they are completely dissolved;
[0125] Z2. Add MgO and Al into the mixing cylinder. 2 O 3 , stir at a low speed of 500 RPM for 45 minutes, let it stand for degassing for 5 minutes, and sieve the material to obtain the second slurry.
[0126] Example
[0127] Example 1
[0128] The raw materials used in this example include: 9 μm polyethylene film 50 mm×50 mm, the first slurry obtained in Preparation Example 1, and the second slurry obtained in Preparation Example 4.
[0129] The preparation method of this embodiment includes:
[0130] S1, covering the polyethylene film with a second covering sheet so that the second covering sheet and the polyethylene film are coaxial, spraying the first slurry on the polyethylene film with a spraying thickness of 1 μm, then removing the second covering sheet, drying the polyethylene film at 75° C., so that the first slurry is dried to form a first coating, and obtaining an intermediate film;
[0131] S2. Cover the first coating layer with a first covering sheet so that the first covering sheet and the polyethylene film are coaxial, spray the second slurry on the polyethylene film with a spraying thickness of 1 μm, then remove the first covering sheet, dry the polyethylene film at 75° C., dry the second slurry to form a second coating layer, and obtain a composite lithium battery separator.
[0132] See also Figure 1 and Figure 2 In the composite lithium battery separator obtained in Example 1, the second coating surrounds the first coating, and the second coating is as thick as the first coating.
[0133] Example 2
[0134] The difference between this embodiment and embodiment 1 is that the spraying thickness in step S1 is 2 μm, and the spraying thickness in step S2 is 2 μm.
[0135] Example 3
[0136] The difference between this embodiment and embodiment 1 is that the spraying thickness in step S1 is 3 μm, and the spraying thickness in step S2 is 3 μm.
[0137] Example 4
[0138] The difference between this embodiment and embodiment 2 is that the first slurry is derived from preparation example 2, and the second slurry is derived from preparation example 5.
[0139] Example 5
[0140] The difference between this embodiment and embodiment 2 is that the first slurry is derived from preparation example 3, and the second slurry is derived from preparation example 6.
[0141] Example 6
[0142] The difference between this embodiment and embodiment 2 is that the first slurry is derived from preparation example 1, and the second slurry is derived from preparation example 7.
[0143] Example 7
[0144] The raw materials used in this example include: 9 μm polyethylene film 50 mm×50 mm, the first slurry obtained in Preparation Example 1, and the second slurry obtained in Preparation Example 4.
[0145] The preparation method of this embodiment includes:
[0146] S1, covering the polyethylene film with a second covering sheet so that the second covering sheet and the polyethylene film are coaxial, spraying the first slurry on the polyethylene film with a spraying thickness of 1 μm, then removing the second covering sheet, drying the polyethylene film at 75° C., so that the first slurry is dried to form a first coating, and obtaining a first intermediate film;
[0147] S2, covering the first coating layer with a first covering sheet so that the first covering sheet and the polyethylene film are coaxial, spraying the second slurry on the polyethylene film with a spraying thickness of 1 μm, then removing the first covering sheet, drying the polyethylene film at 75° C., so that the second slurry is dried to form a second coating layer, thereby obtaining a second intermediate film;
[0148] S3. Spray the first slurry onto the first coating layer and the second coating layer of the second intermediate film with a spraying thickness of 1 μm, and then dry at 75° C. to dry the first slurry, and then grind the edge of the first coating layer to form a convex arc surface on the surface of the first coating layer to obtain a composite lithium battery separator.
[0149] See also Figure 3 , the thickness of the middle part of the composite lithium battery separator is greater than that of the edge.
[0150] Comparative Example
[0151] Comparative Example 1
[0152] The raw materials used in this comparative example include: 9 μm polyethylene film 50 mm×50 mm and the first slurry obtained in Preparation Example 1.
[0153] The preparation method of this comparative example comprises: spraying the first slurry on the surface with a spraying thickness of 1 μm, and then drying at 75° C. to dry the first slurry to obtain a composite lithium battery separator.
[0154] Comparative Example 2
[0155] The difference between this comparative example and comparative example 1 is that the slurry is derived from the second slurry in Preparation Example 4.
[0156] Comparative Example 3
[0157] The raw materials used in this comparative example include: 9 μm polyethylene film 50 mm×50 mm, the first slurry obtained in Preparation Example 1, and the second slurry obtained in Preparation Example 4.
[0158] The preparation method of this comparative example comprises:
[0159] S1, spraying the second slurry on the polyethylene film with a spraying thickness of 1 μm, and then drying at 75° C. to dry the second slurry to form a second coating to obtain an intermediate film;
[0160] S2, spraying the first slurry on the second coating layer with a spraying thickness of 1 μm, and then drying at 75° C. to dry the first slurry to form a first coating layer, thereby obtaining a composite lithium battery separator.
[0161] Comparative Example 4
[0162] The raw materials used in this comparative example include: 9 μm polyethylene film 50 mm×50 mm, the first slurry obtained in Preparation Example 1, and the second slurry obtained in Preparation Example 4.
[0163] The preparation method of this embodiment includes:
[0164] D1, covering the polyethylene film with the fourth covering sheet so that the fourth covering sheet and the polyethylene film are coaxial, spraying the first slurry on the polyethylene film with a spraying thickness of 1 μm, then removing the fourth covering sheet, drying the polyethylene film at 75° C., so that the first slurry is dried to form a first coating, and obtaining an intermediate film;
[0165] S2. Cover the first coating layer with a third covering sheet so that the third covering sheet and the polyethylene film are coaxial, spray the second slurry on the polyethylene film with a spraying thickness of 1 μm, then remove the third covering sheet, dry the polyethylene film at 75° C., dry the second slurry to form a second coating layer, and obtain a composite lithium battery separator.
[0166] Performance Testing
[0167] The composite lithium battery separators prepared in Examples 1 to 7 and Comparative Examples 1 to 4 were tested as follows:
[0168] ① Test the tensile strength, thermal shrinkage and ionic conductivity of the diaphragm in accordance with the national standard GB / T 36363-2018 "Polyolefin diaphragms for lithium-ion batteries";
[0169] ② The peel strength between the coating and the base film is tested according to the method in GB / T 2792-2014 "Test method for peel strength of adhesive tape";
[0170] ③ The testing equipment is a Wangyan-type air permeability meter, which records the time for 100mL of air to pass through the battery separator at a pressure of 0.05MPa to determine the air permeability of the battery separator (s / 100cc). The air permeability increase value = the air permeability of the battery separator - the air permeability of the base film.
[0171] The test results are as follows:
[0172] Table 1 Properties of composite lithium battery separators prepared in Examples 1 to 7 and Comparative Examples 1 to 4
[0173]
[0174] According to Table 1 above, by comparing Example 1 and Comparative Example 1, it can be seen that the shrinkage rate of the composite lithium battery separator obtained in Example 1 is smaller than that in Comparative Example 1. The possible reason is that the particle size of the second inorganic particles is smaller than that of the first inorganic particles, and the bonding ability of the second coating layer with the base film is improved. Therefore, the second coating layer can support the second region of the base film, which is beneficial to improving the strength of the coating layer.
[0175] It should be understood that the above embodiments are only for illustrating the technical concept and features of the present invention, and their purpose is to enable people familiar with this technology to understand the content of the present invention and implement it accordingly. It cannot be determined that the specific implementation of the present invention is limited to these descriptions. For ordinary technicians in the technical field to which the present invention belongs, some simple deductions or substitutions can be made without departing from the concept of the present invention. All equivalent changes or modifications made according to the spirit of the present invention should be covered within the protection scope of the present invention.
Claims
1. A composite lithium battery separator, characterized in that: include: A base film, wherein a first region and an annular second region are arranged on at least one side of the base film, the first region is circular, and the second region surrounds the first region; the first region is coated with a first coating, and the second region is coated with a second coating; The first coating layer includes first inorganic particles, the second coating layer includes second inorganic particles, the first inorganic particles and the second inorganic particles are both inorganic ceramic particles, and the particle size of the second inorganic particles is smaller than that of the first inorganic particles.
2. A composite lithium battery separator according to claim 1, characterized in that: The first inorganic particles are selected from one or more of SrTiO3, SnO2, CeO2, MgO, NiO, CaO, ZnO, ZrO2, Y2O3, Al2O3, TiO2, SiC, AlOOH, and SiO2; and / or, the particle size of the first inorganic particles is 0.2 μm to 0.5 μm; And / or, the thickness of the first coating layer is 1 μm to 3 μm.
3. A composite lithium battery separator according to claim 1, characterized in that: The second inorganic particles are selected from one or more of SrTiO3, SnO2, CeO2, MgO, NiO, CaO, ZnO, ZrO2, Y2O3, Al2O3, TiO2, SiC, AlOOH, and SiO2; and / or, the particle size of the second inorganic particles is 0.05 μm to 0.3 μm; And / or, the thickness of the second coating layer is 1 μm to 3 μm.
4. A composite lithium battery separator according to claim 1, characterized in that: The surface of the second coating layer is coated with the first coating layer.
5. A composite lithium battery separator according to claim 4, characterized in that: The thickness of the first coating in the first region is greater than the thickness of the first coating on the second coating surface, and the first coating on the second coating surface and the first coating in the first region together form a convex surface.
6. A composite lithium battery separator according to claim 1, characterized in that: The second coating has a greater thermal conductivity than the first coating.
7. A composite lithium battery separator according to claim 1, characterized in that: The second inorganic particles have various particle sizes.
8. A method for preparing a composite lithium battery separator as claimed in claim 1, characterized in that: The steps include: Preparing slurry: Preparing the first inorganic particles into a first slurry, and preparing the second inorganic particles into a second slurry; Coating the first area: after covering the second area of the base film, coating the first slurry on the first area, then removing the cover and drying the base film to obtain an intermediate film; Coating the second area: After covering the upper surface of the first coating layer of the intermediate film, coating the second slurry on the second area, then removing the covering and drying the base film to obtain a composite lithium battery separator.
9. The preparation method according to claim 9, characterized in that: The drying temperature is 60°C to 90°C.
Citation Information
Patent Citations
Multilayer porous film, separator for nonaqueous electrolyte secondary batteries, and nonaqueous electrolyte secondary battery
CN103717390A
Lithium ion battery composite membrane and preparation method thereof
CN105958000A
Diaphragm structure
CN108011067A
Diaphragm, roll core and battery
CN115411456A
Separator for power storage device and power storage device comprising same
CN116569294A